1990
DOI: 10.1139/o90-121
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of different isoforms of bovine cathepsin B

Abstract: A rapid purification procedure is described for cathepsin B from bovine liver. After preparation of crude lysosomal extracts, the method only involves DEAE Zeta-Prep-Disk chromatography, gel filtration, and fast protein liquid chromatography on Mono-S column. Two active peaks (P1 and P2) of cathepsin B were distinguished. Both presented uncleaved (relative mass (Mr) 30,000) and cleaved (Mr 25,000 + Mr 5000) chains, but different isoforms as revealed by isoelectrofocusing. These two different populations of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…The 5 kDa light chain does not stain very strongly, and is easily distinguished on the gel. A similar result was obtained by Deval et at. (1990) who also isolated cathepsin B from bovine liver.…”
Section: Resultssupporting
confidence: 91%
“…The 5 kDa light chain does not stain very strongly, and is easily distinguished on the gel. A similar result was obtained by Deval et at. (1990) who also isolated cathepsin B from bovine liver.…”
Section: Resultssupporting
confidence: 91%
“…Different isoforms (charged forms) of cath B may therefore not be the only ones responsible for the change in substrate specificity. This is further supported by the findings of Deval et al (1990) who demonstrated two different purified isoforms of cath B with very similar pH optimum profiles, and that one single isolated isoform of cath B may display a pH profile with 'shoulders' in the acidic and in the slightly alkaline range. Hasnain et al (1992) found that British Journal of Cancer (1997) 75(8) Werle et al, 1995;Ledakis et al, 1996) (Sheahan et al, 1989), who found that the tumour cath B activity at pH 8.0 was more stable than in adjacent colon tissue.…”
Section: Discussionsupporting
confidence: 67%
“…These substrates for Cathepsin B were not compared in controlled experiments before, though there was Cathepsin B activity reported on a variety of short peptides, with a typical k cat ranging from 1 to 364 s –1 and K M from 108 to 1190 μM, which vary by enzyme source and test conditions (Table S1). These comparisons would help identify whether mAb carrier is a factor impacting drug release rate and, therefore, inform the design of ADC constructs.…”
Section: Introductionmentioning
confidence: 99%